2012
DOI: 10.1071/an12006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of body measurements using digital image analysis in female Holstein calves

Abstract: The objective of this study was to determine the accuracy of body measurements (BM) in Holstein female calves using digital image analysis. BM including body length, wither height, chest depth, hip height, and hip width of calves were recorded by stick and tape measurements at birth, weaning and 24 weeks of age. Then photos of calves were taken while calves were standing in a squeeze chute by a digital camera and were analysed by image analysis software to obtain BM of each calf from the image in centimetres. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(9 reference statements)
1
6
0
1
Order By: Relevance
“…The results of the final body weight of the preweaning calves in the recent study were under the result reported by many researchers (Ghassemi Nejad et al, 2013;Tao et al, 2018;de Assis Lage et al, 2019;Wickramasinghe et al, 2019), i.e. in the range of 44 -80 kg.…”
Section: Body Weightsupporting
confidence: 73%
“…The results of the final body weight of the preweaning calves in the recent study were under the result reported by many researchers (Ghassemi Nejad et al, 2013;Tao et al, 2018;de Assis Lage et al, 2019;Wickramasinghe et al, 2019), i.e. in the range of 44 -80 kg.…”
Section: Body Weightsupporting
confidence: 73%
“…In another study, Negretti et al (2008) reported that computerized image analysis was an effective measuring system for determination of LW of buffalo species. Ozkaya (2012) indicated that the digital image analysis provides very close agreement and reality for prediction of BMs of Holstein female calves.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Ozkaya (2012) determined the accuracy of BMs in Holstein female calves using digital image analysis. The best prediction equations for LW were obtained from BMs including BL, WH, CD, HH and HW.…”
Section: Methodsmentioning
confidence: 99%
“…Metode ini dilakukan dengan mengambil foto secara proporsional dan memiliki acuan standar pengukuran sehingga pada saat dilakukan pengukuran secara digital dapat diperoleh data akurat yang mewakili ukuran yang sebenarnya. Metode ini diharapkan dapat diterapkan untuk pengukuran morfometrik yang lebih aman, data yang lebih akurat, dan ternak yang dapat diukur pada waktu yang sama dapat lebih banyak serta dapat memberikan data lebih banyak yang tidak dapat diambil pada pengukuran langsung (Ozkaya 2012).…”
Section: Pendahuluanunclassified